An investigation on the role played by local authorities in service delivery: a case of Kadoma city council. - Nyoni, Vanessa Gladys (Midlands State University, 2018)
The research investigated the role played by local authorities in service delivery using a case study of Kadoma City Council. The study analyzed different sources of service delivery and their contribution to the community at large. The research aimed at bringing out the understanding of the role of local authorities including the factors and causes of poor service delivery which was reviewed and discussed .The role of local authorities in service delivery is vital to human development. Hence the study was not only meant to highlight the role of local authorities in service delivery but also its effectiveness and reasons to poor service delivery. A preview on definition of services, service delivery and local government was highlighted in this study. The preview was aimed at understanding the nature of services and characteristics of service delivery by local authorities .The local authorities legislative framework was also highlighted which safe guards the service system to the community and brings out the role of local authorities, service delivery has since been poor and ill managed hence the various factors, causes and challenges were reviewed in the study. The effects of poor service delivery can be amounted to continuous disease outbreaks for example cholera and typhoid within communities. In understanding the local authorities‟ role in service delivery an assessment on developed and developing countries was outlined for a broader understanding of the study research. A theory was used as a support base of the thesis. A research design was used in accordance with the case study for the investigation, both qualitative and quantitative research methods were used to gather data with the use of secondary and primary sources to bring out a detailed in-depth analysis. Questionnaires, observations and interviews were used to gather information from a selected population sample .A target population constituted of permanent residence of Kadoma urban as well as councilors and council employees.85 questionnaire were administered, were necessary the research used the native language for interpretation of the questions to some residents. Tables, bar graphs and pie charts were used for the presentation of data which was obtained in the field. Data collected from the field was analyzed and summarized. The data collected the possible reason for poor services delivery in Kadoma urban was noted and challenges which are financial, political and corruption rose. Hence the researcher gave recommendations to address the possible challenges being faced by local authorities.